Streptomyces learnhanii sp. nov., unveiling a Mangrove-Derived Novel “Modern Actinobacteria” in Malaysia - Jodi Woan-Fei Law; Vengadesh Letchumanan; Kar-Wai Hong; Sunny Hei Wong; Nurul Syakima Ab Mutalib; Ya-Wen He; Kok-Gan Chan; Loh Teng-Hern Tan (Progress in Microbes and Molecular Biology)
Streptomyces learnhanii sp. nov. MUM 203JT was isolated from Malaysia mangrove soil. This Gram-positive bacterium produces pale greenish-yellow aerial and greyish-yellow substrate mycelia on ISP 2 agar. The taxonomy status of strain MUM 203JT was determined via a polyphasic approach comprising phenotypic observations, genomic and phylogenetic analyses, and chemotaxonomic analyses. The strain demonstrated typical Streptomyces features based on a series of phenotypic and chemotaxonomic evaluations. In particular, the cell wall peptidoglycan contained LL-diaminopimelic acid, and the predominant menaquinones detected include MK9(H8). Analysis of whole-cell sugars revealed the presence of glucose, ribose and mannose. The polar lipid profile of the strain comprised lipid, glycolipid, phospholipid, phosphatidylglycerol, phosphatidylinositol, phosphatidylethanolamine, phosphoglycolipid, and diphosphatidylglycerol. The major cellular fatty acids (>10.0 %) were anteiso-C15:0 (24.7 %), anteiso-C17:0 (16.4 %), iso-C16:0 (15.7 %), iso-C15:0 (11.5 %), and C16:0 (11.1 %). The closely related type strains for strain MUM 203JT, as determined by phylogenetic analysis, include Streptomyces coeruleorubidus JCM 4359T (98.8 %), Streptomyces coeruleoprunus JCM 6919T (98.5 %), Streptomyces thermocarboxydovorans NBRC 16324T (98.1 %). The DNA–DNA relatedness values between strain MUM 203JT and closely related type strains ranged from 10.7 ± 0.6 % to 23.3 ± 4.7 %. Strain MUM 203JT has a genome size of 6,446,886 bp, with DNA G + C content of 72.26 mol%. Based on the polyphasic study of strain MUM 203JT, it can be concluded that this strain represents a novel species, for which the name Streptomyces learnhanii sp. nov. is proposed. The type strain is MUM 203JT (= NBRC 114250T = MCCC 1K04200T).